2021
DOI: 10.1021/acsabm.1c00821
|View full text |Cite
|
Sign up to set email alerts
|

Thickening of Ectatic Cornea through Regeneration Using Decellularized Corneal Matrix Injectable Hydrogel: A Strategic Advancement to Mitigate Corneal Ectasia

Abstract: Ectatic corneal diseases are a group of eye disorders characterized by progressive thinning and outward bulging of the cornea, resulting in vision impairment. A few attempts have been made to use cornea-derived extracellular matrix hydrogels for corneal tissue engineering; however, no studies have investigated its application in corneal ectasia. In this study, we have first developed an animal surgical model that mimics a few specific phenotypes of ectatic cornea. Later, we investigated the potential of decell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Moreover, the reported DNA value for the H/H protocol is between the two commercially available products Alloderm ™ (0.95 μg/mg) and Permacol ™ (0.063 μg/mg) 10 . The use of sodium chloride as a lone decellularizing agent has been shown to be effective without eliciting the immune response in an in vivo study as reported in literature 28 . The ECM components that help in gel formation via self‐assembly, responsible for lubrication and harbor various growth factors were retained in the decellularized tissue.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Moreover, the reported DNA value for the H/H protocol is between the two commercially available products Alloderm ™ (0.95 μg/mg) and Permacol ™ (0.063 μg/mg) 10 . The use of sodium chloride as a lone decellularizing agent has been shown to be effective without eliciting the immune response in an in vivo study as reported in literature 28 . The ECM components that help in gel formation via self‐assembly, responsible for lubrication and harbor various growth factors were retained in the decellularized tissue.…”
Section: Discussionmentioning
confidence: 70%
“…10 The use of sodium chloride as a lone decellularizing agent has been shown to be effective without eliciting the immune response in an in vivo study as reported in literature. 28 The ECM components that help in gel formation via self-assembly, responsible for lubrication and harbor various growth factors were retained in the decellularized tissue. Compared to dSMM prepared by S/T method, complete solubilization of lyophilized tissue in 0.1 M HCl was observed for dSMM by H/H method with no remnants of the tissue pieces, probably because of the salting-in effect.…”
Section: Discussionmentioning
confidence: 99%